Dual‐Functional Metasurface toward Giant Linear and Circular Dichroism. Issue 11 (29th March 2020) - Huang, Yijia; Xie, Xin; Pu, Mingbo; Guo, Yinghui; Xu, Mingfeng; Ma, Xiaoliang; Li, Xiong; Luo, Xiangang
Abstract: As a kind of artificial surface composed of subwavelength meta‐atoms, metasurface has shown great potential in full vectorial electromagnetic manipulation. Here, a dual‐functional metasurface that is capable of generating 97% linear dichroism and 87% circular dichroism in the infrared region is proposed. The two functionalities can be achieved simultaneously under incident light of vertical azimuthal angles. Subsequent simulations demonstrate that the giant dichroism is induced by symmetry breaking of the structure under oblique incidence. Compared with single‐functional metasurfaces, this device exhibits better performance and more functionalities without the sacrifice of compactness. It is believed that this dual‐functional metasurface with simple geometry can find many potential applications in various fields, ranging from analytical chemistry and imaging to sensing and spectroscopy. Abstract : A dual‐functional metasurface is proposed that can achieve giant linear and circular dichroism simultaneously. The two operation modes can be tuned by simply changing the incident azimuthal angles. Polarization‐selective absorption is demonstrated both numerically and experimentally in the IR region. All these merits offer a wide range of fascinating integration applications in spectroscopy, imaging, sensing, and polarimetry.